Computer Science Education in Secondary Schools--The Introduction of a New Compulsory Subject - Hubwieser, Peter (ACM transactions on computing education, 2012)
In 2004 the German state of Bavaria introduced a new compulsory subject of computer science (CS) in its grammar schools ("Gymnasium"). The subject is based on a comprehensive teaching concept that was developed by the author and his colleagues during the years 1995-2000. It comprises mandatory courses in grades 6/7 for all students of grammar schools and in grade 9/10 for the students of the science and technology track of this school type. In grades 11 and 12 there are elective courses that qualify for an optional graduation exam in CS. The first students that have attended the course in total graduated in 2011. This article describes the whole project in the form of an extensive case study that is guided by the "Darmstadt Model," which was developed as a category system for computer science education in secondary schools by a working group at ITiCSE 2011. This case study is the first (nearly) all-embracing discussion of the whole project that describes the long way from the original concept to the first graduates as well as the internal structure of the subject and the first results. (Contains 11 figures, 10 tables and 5 footnotes.)